Response of Chinese Cabbage (Brassica rapa var. pekinensis) to Zinc Sulfate and Nano Zinc Oxide Fertilization and Their Effects on Growth and Yield - Abrar A. Naser; Aws Jawad Kadhim; Ashjan Nazar Kamil; Sabreen Mohammed Lateef; Hayder Bahjat Nasih; Abrar A. Naser; Aws Jawad Kadhim; Ashjan Nazar Kamil; Sabreen Mohammed Lateef; Hayder Bahjat Nasih (Jurnal MIPA dan Pembelajarannya, 2026)
The objective of the study was to evaluate field growth and yield response of ZnO-NPs and ZnSO4 applied at various concentrations on Chinese cabbage during 2024/25. A randomized block design with three replications (8 treatments: selections including 25, 50, 75 and 100 mg/L zinc source concentrations) was employed to evaluate the increasing effect of ZnSO4 treatment as compared to the control in different traits. Among all the treatments, the treatment consisted of CA and MA maintained good vegetative growth on all growth parameters such as average bulb weight (2.86 kg/plant), marketable bulb weight (2.54 kg/plant), bulb circumference (48.7 cm) and number of leaves (19.6 leaves/plant). In addition, it also produced highest total yield (82.4 t·ha⁻¹) and marketable bulb yield (73.2 t·ha⁻¹) compared to the other treatments. This is due to the importance of zinc ions for enzyme activation in chlorophyll biosynthesis. This improves photosynthesis and protein synthesis as a positive effect on vegetative growth and headformation. the other hand, the efficiency of nano-zinc oxide slacking off at higher amounts d which there is probability in aggregation of nanoparticles and thereby obstacle it absorption on the other vital elements. It has been reported that 75 mg·L⁻¹ zinc sulfate might be the best concentration for growth characteristics and yield of Chinese cabbage. This further highlights the significance of choosing an appropriate source of zinc for promoting greater absorption and bestowing positive physiological effects.